2018
DOI: 10.17219/acem/94157
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Th1/Th2 and related cytokines: Prediction value in postoperative febrile UTI after ureteroscopy in patients with ureteral calculi

Abstract: Background. The topic of whether preoperative Th1/Th2 cells and their related factors have a predictive value for postoperative febrile urinary tract infection (UTI) in patients with ureteral calculi has not been explored. Objectives. The objective of this study was to investigate the role of preoperative Th1/Th2 cells and related cytokines in the prediction of postoperative febrile UTI after ureteroscopy in patients with ureteral calculi. Material and methods. One hundred sixty patients who underwent ureteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Th1 Responses Promoting Bacterial Clearance. In view of the finding that the bladder's natural adaptive immune response to infection is Th2-biased, which inhibits Th1-mediated bacterial clearance capacity (7,27), we reasoned we could modify this response through vaccination. We hypothesized that bacteriaspecific immune responses with enhanced bacteria-clearing capacity could be evoked by immunizing mice with bacterial antigens accompanied by a known Th1-polarizing adjuvant.…”
Section: Local Vaccination With Th1-polarizing Adjuvant Can Evoke Bladdermentioning
confidence: 99%
See 2 more Smart Citations
“…Th1 Responses Promoting Bacterial Clearance. In view of the finding that the bladder's natural adaptive immune response to infection is Th2-biased, which inhibits Th1-mediated bacterial clearance capacity (7,27), we reasoned we could modify this response through vaccination. We hypothesized that bacteriaspecific immune responses with enhanced bacteria-clearing capacity could be evoked by immunizing mice with bacterial antigens accompanied by a known Th1-polarizing adjuvant.…”
Section: Local Vaccination With Th1-polarizing Adjuvant Can Evoke Bladdermentioning
confidence: 99%
“…Mice Heavily Programmed to Evoke a Strong Th2 Response. Recent studies have revealed that mice subjected to multiple UTIs are heavily programmed to evoke a powerful Th2 response with limited capacity to clear infections (7,27). This condition is closely reminiscent of subjects prone to recurrent UTIs, in whom each infectious bout predisposes to another infection (1-6).…”
Section: Vaccination With Cpg Can Induce Protective Th1 Responses Even Inmentioning
confidence: 99%
See 1 more Smart Citation